Marketing practices of professional engineering consulting firms: Implement or not to implement? - Jaafar, Mastura; Aziz, Abdul Rashid Abdul; Wai, Andy Lian Shin (Journal of Civil Engineering and Management, 2008)
This article explores the necessity of applying marketing practices by engineering consulting firms that serve the construction industry. Most construction professionals perceive marketing as an unimportant management function. The present study provides support to similar previous studies conducted in other countries which found marketing is more ‘trappings’ rather than ‘substance’. Stiff competition drives civil and structural engineering (C&S) firms in Malaysia to suit their marketing practices in ensuring survival. In relation to this, company profile or characteristics such as firm organization, operational structure and nature of environment help providing an explanation on the readiness of these firms to fully implement marketing practices. The results also suggest that these firms use minimal marketing with the professional image projected by the directors or principals as playing an important role. Rinkodaros praktika profesionaliose inžinerijos konsultacinėse įmonėse: taikyti ją ar jos netaikyti? Santrauka. Nagrinėjama rinkodaros praktikos taikymo būtinybė statybos pramonės inžinerinėse konsultacinėse įmonėse. Dauguma statybos specialistų rinkodarą vertina kaip nelabai svarbią valdymo funkciją. Šis tyrimas patvirtina jau anksčiau kitose šalyse atliktų tyrimų rezultatus. Šiais tyrimais nustatyta, kad rinkodara yra daugiau „puošmena“ nei esminis valdymo kriterijus. Dėl nelanksčios inžinerijos ir statybos įmonių konkurencijos Malaizijoje būtina taikyti marketingo praktiką. Todėl suformuotas įmonės įvaizdis, įmonės organizacinė ir veiklos struktūra, mikroaplinka rodo įmonės rinkodaros taikymo pasirengimą. Gauti rezultatai rodo, kad įmonėse, kuriose dėl aukštos kvalifikacijos valdininkų sudarytas profesionalumo įvaizdis, rinkodaros lygis yra silpnas. Reikšminiai žodžiai: rinkodaros praktika, statybos inžinerijos konsultacinės įmonės, statybos pramonė. First Published Online: 14 Oct 2010